Some issues on stakeholder engagement in science technology and innovation policymaking processes for sustainable development goals - Dang Thu Giang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
In the context that the world is facing social challenges and rapidly increasing uncertainty, researchers on science technology and innovation (STI) policy are concerned with building STI policies capable of orienting innovation, mitigating socio-technical constraints, promoting resilience and prevent risks, uncertainty and ignorance. In order to develop STI policies that meet these requirements, participation and cooperation among stakeholders in the STI policymaking process plays an increasingly important role. This article aims to overview some issues of stakeholder participation in the STI policymaking process and propose some contents that need attention for research in the coming time on the engagement of stakeholders in the policymaking process in Vietnam. Code: 23092601